The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/ajhp/zxab109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the timing of MRSA PCR nasal screening: How long can a negative assay be used to rule out MRSA-positive respiratory cultures?

Abstract: Purpose Previous studies indicate that the polymerase chain reaction (PCR) nasal assay for methicillin-resistant Staphylococcus aureus (MRSA) has a consistently high (>95%) negative predictive value (NPV) in ruling out MRSA pneumonia; however, optimal timing of PCR assay specimen and respiratory culture collection is unclear. Methods A study including 736 patients from a community hospital system was conducted. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…A recent study reported an NPV of 95.5% when the time between MRSA nares and respiratory sample collection was 14 days. 6 We found that history of MRSA infection and time of ≥7 days between swab and respiratory culture were associated with discordance. However, the low event rate limits the ability to control for other confounders and interpretation of findings should be approached carefully based on the nature of the retrospective design.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…A recent study reported an NPV of 95.5% when the time between MRSA nares and respiratory sample collection was 14 days. 6 We found that history of MRSA infection and time of ≥7 days between swab and respiratory culture were associated with discordance. However, the low event rate limits the ability to control for other confounders and interpretation of findings should be approached carefully based on the nature of the retrospective design.…”
mentioning
confidence: 74%
“… 3–6 However, concerns for swab and respiratory culture discordance remain, and there are a few known risk factors associated with discordant results. 4 , 6 We conducted a single-centre, retrospective, case–control study to evaluate predictors of having a discordant result (negative MRSA nares swab with a positive MRSA respiratory culture) in patients diagnosed with pneumonia. Chi-squared and Fisher’s exact test were used to compare categorical variables and Mann–Whitney U -test was used for continuous variables.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were excluded if confirmatory cultures were not obtained within 2 weeks from the MRSA NaPCR test. 16 Qualifying culture sites included respiratory (bronchoalveolar lavage, sputum, and tracheal aspirate), blood (venous puncture or lines), urine, skin and skin structure (including wound), and intra-abdominal. Augusta University (AU) Medical Center is a 483-bed urban, tertiary referral, academic medical center.…”
Section: Methodsmentioning
confidence: 99%
“…The Division of Healthcare Quality Promotion within the Centers for Disease Control and Prevention (CDC) has underscored the importance of advancing diagnostic stewardship to enhance treatment, outcomes, and patient safety. 1,2 A recent study conducted by Turner et al 3 assessed the extent to which the nasal methicillin-resistant Staphylococcus aureus (MRSA) polymerase chain reaction (PCR) maintained its negative predictive value (NPV) in ruling out MRSA-positive respiratory cultures relative to the duration of hospitalization. The study highlighted a high NPV of 95.7% from 49 hours to 7 days and 92.9% from 8 to 14 days.…”
mentioning
confidence: 99%